1-Oxo-2, 2, 6, 6-tetramethylpiperidinium bromide converts α-H N, N-dialkylhydroxylamines to nitrones via a two-electron oxidation mechanism. Issue 1 (December 2018) - Stoyanovsky, Anastas; Stoyanovsky, Detcho
Abstract Herein we provide experimental proof that 1-oxo-2, 2, 6, 6-tetramethylpiperidinium bromide converts α-HN, N -dialkylhydroxylamines to nitrones via a two-electron oxidation mechanism. The reactions reported are rapid, proceed under mild conditions, and afford nitrones in excellent yields.